(untitled) (Huellas, 2021)
Throughout urban history, cities have been instrumental in ensuring the reproduction of existing forms of accumulation. At present, State and market play complementary roles in the maximization of urban income in favour of the latter. In this respect, this work aims to account for two forms of urban intervention strongly fostered by the local State, which differ from one another in substantial aspects, promoting particular political articulations that impact on the territory generating urban, political, institutional, symbolic and environmental ruptures. In this way, based on the analysis of the State habitational program Pro.Cre.Ar and the Distrito Sustentable project, we will account for the local State practices that affect the urban structure of the Ciudad de Mendoza, Argentina. We hold that these practices are related to the city’s urban politics that generate favorable conditions for the raising of urban income by private agents.